Investigation of oxidation and electrical behavior of AISI 430 steel coated with Mn–Co–CeO2 composite. (24th January 2020) - Mosavi, Ali; Ebrahimifar, Hadi
Abstract: Ferritic stainless steels, under the working conditions of solid oxide fuel cells, form a chromium oxide layer. This layer has a low electrical conductivity and consequently reduces the efficiency of these energy converters. An action to improve the properties of the connecting plates is to use a conductive and protective layer of coating. In this study, AISI 430 stainless steel was coated with Mn–Co–CeO2 through electroplating technique. To evaluate the oxidation behavior, isothermal and cyclic oxidation tests were used at 800 °C. Area specific resistance (ASR) of uncoated and coated specimens was also compared as a function of time during oxidation at 800 °C. Coating microstructure and oxidized samples were examined by scanning electron microscopy (SEM) and X-ray diffraction (XRD) device. In isothermal oxidation, uncoated samples had more weight gain than the Mn–Co–CeO2 coated samples. The coating layer improved oxidation resistance by limiting the diffusion of chromium cation and oxygen anion. The cyclic oxidation results showed that the Mn–Co–CeO2 coated samples had a very good resistance to cracking and spallation. Also, the results of ASR showed that formation of MnCo2 O4 and MnFe2 O4 spinels and also the presence of CeO2 resulted in reduction of area specific resistance. ASR for samples coated with Mn–Co–CeO2 and uncoated samples was 12.4 mΩ.cm 2 and 38.7 mΩ.cm 2, respectively after 200 h of oxidation at 800 °C. Highlights: Fabrication of Mn–Co–CeO2 composite coating on AISI 430 steel. Formation of MnCo2 O4 and MnFe2 O4 Spinels during isothermal oxidation. Improvement of isothermal and cyclic oxidation resistance of coated samples. Improvement of electrical conductivity of coated AISI 430 steel.